PENGGUNAAN METODE KELOMPOK PENASEHAT DALAM MENINGKATKAN PRESTASI BELAJAR KELAS VIII PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS DARUSSALAM DESA PEMAT DUKU TIMUR KABUPATEN BENGKALIS - Afifa, Siti Nur; Ritonga, Supadi (STAI Darul Qalam Tangerang, 2023)
This study raised the title of using the advisory group method in improving learning achievement of keals VIII at MTS Darussalam, Pematang Duku Timur Village, Bengkalis District. This research seeks to provide updates to the implementation of learning. The research was conducted because there are still some educators who have not consistently used innovative learning models in the classroom. This study aims to find out how the use of the advisory group method in providing an increase in student achievement in the subjects of moral creed and find out whether there is an increase between student achievement in the subjects of moral creed. This research is included in the type of experimental quantitative research, which uses tests and documentation in its data collection. In analyzing the collected data, a t-test is used to see the comparison of students' pretest and posttest scores. The results of the analysis using an independent t-test and obtained a significance value of 0.502>0.05, so that Ha in this study, was accepted. The effectiveness of the advisory group's learning method can also be seen through the average score of moral creed subjects in the experimental group was 77.97 higher than the control group which had an average score of 66.88. From these results, it can be concluded that the advisory group method can improve student achievement in the subjects of moral creed at MTS Darussalam, Pematang Duku Timur Village, Bengkalis District